2007
DOI: 10.1197/j.aem.2007.08.007
|View full text |Cite
|
Sign up to set email alerts
|

End‐tidal Carbon Dioxide Measurements in Children with Acute Asthma

Abstract: Noninvasive bedside measurement of EtCO2 values among children with acute asthma is feasible. EtCO2 values did not distinguish children with mild disease from those with more severe disease. Further data are needed to clarify the association between EtCO2 values and other indicators of disease severity, particularly in children with more severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…When evaluating the use of capnometry in asthma, a similar obstructive lung disease in children, the results were similar. Guthrie et al [24] measured EtCO 2 in children with acute asthma attack, and demonstrated that EtCO 2 values did not distinguish children with mild asthmatic disease from those with a more severe disease. It becomes evident that this type of measurement is not enough to assess clinical severity.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating the use of capnometry in asthma, a similar obstructive lung disease in children, the results were similar. Guthrie et al [24] measured EtCO 2 in children with acute asthma attack, and demonstrated that EtCO 2 values did not distinguish children with mild asthmatic disease from those with a more severe disease. It becomes evident that this type of measurement is not enough to assess clinical severity.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, it's been clear that the capnogram can be used to track inflammatory states in cardiopulmonary illnesses. Guthrie et al ( 2007 ) used a microcap plus device (Oridion Capnograph, Israel) to measure EtCO 2 in 16 asthmatic patients and concluded that non-invasive EtCO 2 assessment at the bedside is possible in children with acute asthma. Nagurka et al ( 2014 ) researched the effects of extreme (low and high) EtCO 2 on 299 asthmatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, around 0.25 million people die each year prematurely due to improper management and lack of personal asthma monitoring tool. As well Kaitlin and Krull suggested that young adults (age [18][19][20][21][22][23][24][25] suffering from asthma should have a personal asthma monitoring device to assess their disease and decrease their risk of exacerbation and hospital admission [4]. Hence the early diagnosis of asthma and achieving acceptable asthma supervision at the right time remains evasive despite the existing methods.…”
Section: Introductionmentioning
confidence: 99%
“…A Recent study shows that the capnograph can be considered as a new method to monitor the asthmatic condition [10][11][12][13][14][15][16][17][18][19][20][21][22]; as it uses an infrared technology to measure the concentration of carbon dioxide during exhalation and helps to understand the respiratory status of the patients including asthma [23]. However, most of the studies were offline.…”
Section: Introductionmentioning
confidence: 99%